First approach for soil to conilon coffee in the atlantic region of Bahia - Cayô Cavalcanti, André; Góes de Oliveira, Marcos; Monzoli Covre, André; Gontijo, Ivoney; Braun, Heder; Partelli, Fábio Luiz (Coffee Science - ISSN 1984-3909, 2017)
The Integrated Diagnosis and Recommendation (DRIS), although commonly used in the interpretation of leaf analysis has also been employed in chemical analysis of soil, as there is potential for the use of the methodology also in soil and coffee. This study aimed to establish DRIS sufficiency ranges and standards for soils under conilon coffee in the Atlantic region of Bahia State. Forty eight samples of soil were collected in two years at a depth of 0-20 cm. Amounts of organic matter, Ca, Mg , K, P, S , Zn, Cu, Fe, Mn, bases and saturation capacity cation exchange at pH 7 were quantified. It managed to establish DRIS and soil sufficiency ranges from crops to productivity, equal and more than 100 ha-1 bags of coffee conilon, which are applicable in the fertilizer recommendation of this culture in the region. Most parameters set presented discrepancy in relation to the theoretical framework that currently has to conilon coffee. The results suggest the development of regional and specific rules for the application of DRIS and band of sufficiency on the ground to conilon coffee plantations.